Power Relations in Sexual Violence According to Ministry of Education, Culture, Research, and Technology Regulation Number 30 0f 2021 - Meliana, Sherly; Tria Anendri, Nesa; Corina Olga, Niken; Efritadewi, Ayu; Niko, Nikodemus (LPPPIPublishing, 2024)
The incidence of sexual violence is on the rise, impacting both adults and children, posing a significant societal threat. Rooted in power dynamics, this violence extends beyond educational campuses to various societal contexts. This study endeavors to investigate the influence of power dynamics on sexual violence. Utilizing normative legal research techniques and surveys, the study aims to yield insightful conclusions. It is evident that power dynamics often culminate in violent acts. Sexual violence within educational institutions has profound repercussions for both victims and the institutions themselves. Furthermore, power imbalances exacerbate the trauma experienced by victims. Implementing stringent regulations is essential for prosecuting perpetrators of sexual violence. Ultimately, this contributes to enhancing legal awareness regarding power dynamics in the context of sexual violence, fostering a safer environment for all individuals.